Automated Mobile Delivery of Financial Incentives for Smoking Cessation Among Socioeconomically Disadvantaged Adults: Feasibility Study - Kendzor, Darla E; Businelle, Michael S; Waring, Joseph J C; Mathews, Ashley J; Geller, Daryl W; Barton, Jocelyn M; Alexander, Adam C; Hébert, Emily T; Ra, Chaelin K; Vidrine, Damon J (JMIR Publications, 2020)
BackgroundSocioeconomic disadvantage is associated with a reduced likelihood of smoking cessation. Smartphone ownership is increasing rapidly, including among low-income adults, and smartphone interventions for smoking cessation may increase access to smoking cessation treatment among socioeconomically disadvantaged adults. ObjectiveThis study aimed to evaluate the feasibility of an automated smartphone-based approach to delivering financial incentives for smoking cessation. MethodsSocioeconomically disadvantaged adults initiating tobacco cessation treatment were followed from 1 week before a scheduled quit attempt through 26 weeks after the quit date. Participants received telephone counseling and nicotine replacement therapy. Smoking cessation was verified 5 times per week via smartphone prompts to self-report smoking status and submit a breath sample via a portable carbon monoxide (CO) monitor that was connected with participants' smartphones. Identity was verified during smoking status assessments using smartphone-based facial recognition software. When smoking abstinence and identity were verified, an automated credit card payment was triggered. Participants were incentivized for abstinence on the quit date and up to five days per week during the first 4 weeks after the scheduled quit date, with additional incentives offered during postquit weeks 8 and 12. In total, participants had the opportunity to earn up to US $250 in abstinence-contingent incentives over the first 12 weeks of the quit attempt. ResultsParticipants (N=16) were predominantly female (12/16, 75%) and non-Hispanic white (11/16, 69%), black (4/16, 25%), or Hispanic of any race (1/16, 6%). Most participants (9/16, 56%) reported an annual household income of <US $11,000. During the first 4 weeks after the scheduled quit date, participants completed a median of 16 (out of 21; range 1-21) mobile smoking status assessments, and they earned a median of US $28 in abstinence-contingent incentives (out of a possible US $150; range US $0-US $135). Median earnings did not change during the 8- and 12-week incentivized follow-up periods (total median earnings over 12 weeks=US $28; range US $0-US $167). During the first 4 weeks after the scheduled quit date, participants abstained from smoking on a median of 5 (out of 21) assessment days (range 0-20). At the in-person follow-up visits, the expired CO-confirmed 7-day point prevalence abstinence rates were 19% (3/16) and 13% (2/16) at 12 and 26 weeks postquit, respectively. Overall, most participants reported that the system was easy to use and that they would recommend this treatment to their friends and family. ConclusionsPreliminary data suggest that this smartphone-based approach to verifying identity and smoking status and automating the delivery of abstinence-contingent incentives to a credit card is feasible for use among socioeconomically disadvantaged adults. However, continued refinement is warranted.